Smart Door Lock System by Using Face Recognition - Amirah Syahirah Ariffin; Norharyati Harum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Security is one of the main concerns to people who resides in a house as there is a lot of cases such as robbery. Thus, the safety of people is the utmost importance. However, people still use the traditional door lock to secure their home. Therefore, this paper presents the idea of using Face Recognition and Telegram application as part of the smart features to enhance the home security. Face Recognition methods that will be used are Local Binary Pattern Histogram (LBPH) which act as feature extraction under local appearance-based techniques and Haar Cascade as a classifier. Besides, the usage of Telegram application will also be utilised. As the output, the Face Recognition technology is being used to grant authorized user access to the house and the Telegram application is being used to remotely control the door lock without any keys. In conclusion, by implementing those advanced technologies it will strengthen the security of the home as well as the wellbeing of the people.